Effect of genotype and egg weight on hatchability properties and embryonic mortality pattern of native chicken populations - Moataz Fathi; Osama Abou-Emera; Ibrahim Al-Homidan; Ahmed Galal; Gamal Rayan (Poultry Science, 2022)
ABSTRACT: Fertility and hatchability are 2 major parameters that highly influence the reproductive performance of chicken breeds. The objective of this study is to investigate how the genetic background of chickens affects the aspects of fertility, hatchability, and embryonic mortality pattern. Six different native chicken genotypes (black, black-barred, brown, gray, naked neck, and frizzle) kept under similar conditions were evaluated. A total of 1,645 fertile pedigreed eggs from all genetic groups were collected and incubated in forced draft setter. Fertility, hatchability, embryonic mortality, and hatched chick weight were determined. The data were subjected to a one-way analysis of variance with breed (genotype) as a fixed effect. Sire component of variance were used to compute heritability estimates for hatchability traits. The results showed that the fertility and hatchability of the eggs produced from the naked neck or frizzle genotypes exhibited higher values compared to the other genetic groups. An increase in the relative weight of hatched chicks was detected in hatching eggs weighing 44 g or higher. Therefore, attention should be given to the egg size produced by native chicken populations to achieve maximum hatchability performance. Multiple regression analysis revealed that the settable egg weight and the egg weight loss during incubation are the main factors affecting the relative weight of hatched chicks of all genotypes.